An International Collaborative Initiative to Establish a Quality-of-Life Questionnaire for Children and Adolescents with Repair of Esophageal Atresia in 14 Countries - The International EA-QOL Group (MDPI AG, 2024)
The EA-QOL questionnaire measures quality-of-life specifically for children born with esophageal atresia (EA) aged 8-18 and was completed in Sweden and Germany. This study aimed to describe an international collaborative initiative to establish a semantically equivalent linguistic version of the EA-QOL questionnaires in 12 new countries. The 24-item EA-QOL questionnaire was translated into the target languages and the translated questionnaire was evaluated through cognitive debriefing interviews with children with EA aged 8-18 and their parents in each new country. Participants rated an item as to whether an item was easy to understand and sensitive/uncomfortable to answer. They could choose not to reply to a non-applicable/problematic item and provide open comments. Data were analyzed using predefined psychometric criteria; item clarity ≥80%, item sensitive/uncomfortable to answer ≤20%, item feasibility(missing item responses ≤5%). Decision to improve any translation was made by native experts-patient stakeholders and the instrument developer. Like in Sweden and Germany, all items in the cross-cultural analysis of child self-report (ntot = 82, 4-10 children/country) met the criteria for item clarity in all 12 new countries, and in parent-report (ntot = 86, 5-10 parents/country) in 8/12 countries. All items fulfilled the criteria for sensitive/uncomfortable to answer (child-report 1.2-9.9%; parent-report 0-11.6%) and item feasibility. Poor translations were resolved. Hence, this study has established semantically equivalent linguistic versions of the EA-QOL questionnaire for use in children aged 8-18 with repair of EA in and across 14 countries.